Study of the Effect of Thermomechanical Treatments on the Property of Beryllium Bronze in Order to Expand Its Application - Rakhadilov, B.K.; Kengesbekov, A.B.; Magazov, N.M.; Kusainov, A.A.; Kairbaeva, L.S.; Molbosynov, Y.S. (Karagandy University of the name of academician E.A. Buketov, 2025)
The article is devoted to the study of the influence of thermomechanical treatments on mechanical and physicochemical properties of beryllium bronze in order to expand its application in modern technologies. This paper studies the influence of different modes of thermomechanical processing on the structure and properties of beryllium bronze. The mechanism of influence of these methods on modification of alloy microstructure, which directly affects its performance characteristics, is described. The obtained results allow expanding the areas of application of beryllium bronze in industry, aircraft construction and other sectors. And also the main conclusions are that the introduction of advanced methods of thermomechanical processing helps not only to improve the physical characteristics of bronze, but also makes it possible to use this material in new areas, such as aerospace and automotive industries. The article is of importance for specialists in the field of materials science and engineering, as it provides new data and recommendations that can improve the processes of production and operation of beryllium bronze products.
Термомеханикалық өңдеулердің бериллий қоласының қасиеттеріне әсерін оның қолданылуын кеңейту мақсатында зерттеу
Изучение влияния термомеханической обработки на свойства бериллиевой бронзы с целью расширения области ее применения
Keywords: beryllium bronze; heat treatment; mechanical treatment; thermomechanical treatment; hardening; material microstructure; equal-channel angular pressing (ECAP)